2000
DOI: 10.1002/(sici)1097-4598(200004)23:4<543::aid-mus13>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis IgG-treated neuromuscular junctions develop sensitivity to L-type calcium channel blocker

Abstract: In order to search for early changes induced by the application of human immunoglobulin G (IgG) on motor nerve terminals, IgG from patients with amyotrophic lateral sclerosis (ALS) and control subjects was injected subcutaneously into the levator auris muscle of mice. A week or a month after the last injection, endplate potentials were recorded. No changes in quantal content of transmitter release were observed. In control and ALS IgG-treated muscles, neurotransmitter release remained sensitive to P/Q-type and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Additionally, ALS-IgG consistently increased transmitter release in different NMJ preparations, including diaphragm muscle (Uchitel et al, 1988;O'Shaughnessy et al, 1998;Mohamed et al, 2002;Muchnik et al, 2002) and levator auris muscle of the mouse (Uchitel et al, 1992;Fratantoni et al, 2000) and guinea pig diaphragm muscle (O. D. Uchitel, unpublished results) and even in hippocampal cellular culture (Andjus et al, 1997). It did not increase transmitter release, however, in PC12 cells (Offen et al, 1998) and mouse extraocular NMJ (Mosier et al, 2000).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Additionally, ALS-IgG consistently increased transmitter release in different NMJ preparations, including diaphragm muscle (Uchitel et al, 1988;O'Shaughnessy et al, 1998;Mohamed et al, 2002;Muchnik et al, 2002) and levator auris muscle of the mouse (Uchitel et al, 1992;Fratantoni et al, 2000) and guinea pig diaphragm muscle (O. D. Uchitel, unpublished results) and even in hippocampal cellular culture (Andjus et al, 1997). It did not increase transmitter release, however, in PC12 cells (Offen et al, 1998) and mouse extraocular NMJ (Mosier et al, 2000).…”
mentioning
confidence: 85%
“…The electrophysiological equipments used have been described previously (Fratantoni et al, 2000). Borosilicate glass capillaries were used for microelectrodes filled with 3 M KCl (20 -35 M⍀ resistance).…”
Section: Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have highlighted the relationship between high levels of glutamate released by nerve terminals and an increase in intracellular free calcium due to ALS IgG action on ligand and/or voltage-gated Ca 2+ channels [10][11][12][13][14][15]. In addition, neuronal death due to excitotoxicity has been suggested as the basis of the etiopathogenesis of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that this toxin significantly impaired neurotransmission, by preventing Ca 2+ influx through N-type VGCCs at P8 but not at P14, when the NMJ has developed to maturity and switched to P/Q-type VGCC mediated transmitter release. Both L-and R-type VGCCs have also been implicated in having a minor role in the release of ACh at healthy NMJ (Rosato-Siri & Uchitel, 1999;Correia-deSa et al, 2000a, b;Urbano et al, 2003), while L-type VGCCs also play a role in transmitter release under pathological conditions such as amyotrophic lateral sclerosis (Fratantoni et al, 2000) and in botulinum toxic poisoning (Santafe et al, 2000).…”
Section: Voltage Gated Calcium Channelsmentioning
confidence: 99%